Reviving Heritage Building Façades After Disasters: The Case of Derna Following Storm Daniel in Light of Historic Urban Design Standards (The International Journal of Engineering & Information Technology (IJEIT), 2025)
Historic cities often suffer significant architectural losses during natural disasters, particularly the façades of heritage buildings that embody urban identity and cultural memory. This study aims to explore the potential for reviving historical façades damaged by disasters in accordance with the design standards of traditional urban fabrics, using the case of Derna, Libya, following the 2023 Storm Daniel disaster.The research adopts a multi-layered analytical methodology that combines literature review, architectural analysis, and field documentation, supported by interviews and local sources. It examines the extent of damage to the façades in Derna’s old city and assesses the feasibility of reconstructing them in a way that preserves their original character while meeting contemporary standards of safety and sustainability. Furthermore, the study evaluates the alignment of proposed reconstruction efforts with international heritage charters, and presents a phased implementation plan that includes legal, technical, and community-based recommendations.The findings affirm that revitalising the facades of historic buildings in Derna is not only feasible but vital for restoring the city's collective urban memory—provided that the process follows a scientifically grounded, participatory approach that balances authenticity with innovation.